(untitled) (Research, Society and Development, 2020)
In recent years the pharmaceutical market has grown in a promising way, the large chains of pharmacies, drugstores and the pharmaceutical industry itself have achieved results that generate billions of reais per year and these numbers only tend to grow. This work arose from the need to draw a market profile for the municipality of Teresina-PI in relation to the great expansion of the pharmaceutical market, which in recent years has increased by about two digits, being higher than GDP, with a turnover of 11, 76% in 2018. Its objective is to analyze the growth of drugstores and draw a market profile presenting a survey of how the market has presented itself and in comparison make an analysis of the increase or not of establishment in irregularity, tracing this profile can be demonstrate whether the growth index will guarantee a competitive and quality sector through the services provided by the establishments with regard to drugstores. For the development of the project, comparative data will be analyzed together with the responsible bodies with respect to GEVISA, Jucepi and CRF-PI, where a profile of the drugstore market in the municipality and the state of regularity of both will be drawn. The results are expected to be positive in relation to growth and the degree of regularity that is extremely essential for health promotion. The motivation of the research was due to the need to demonstrate data that are not presented by any specific research and that is of great interest to the bodies linked to the pharmaceutical sector, in addition to demonstrating that the market is favorable for more investments in the sector.